GINKGO BILOBA EXTRACT INFLUENCE ON POST TRAUMATIC STRESS - Murthy TEGK, Jithendra Chimakurthy*, (Journal of Pharmaceutical Research and Opinion, 2014)
Low cortisol levels have been reported in post-traumatic stress despite increased corticotrophin releasing factor secretion in contrast with depression where an increased cortisol levels were observed. This could be due to the exaggerated negative feedback mechanism on the HPA axis. In the present study the effect of Ginkgo biloba extract on post-traumatic stress induced with predator scent induced stress model in rats after short term and long term treatment and the effect on the serum cortisol levels were estimated. The protective effect of the extract on trauma was studied using elevated plus maze and was significant with long term treatment. A significant increase in the cortisol levels were observed on long term treatment with the extract and no changes were observed in the rats unexposed to the predator scent. This increase in the cortisol levels may be due to the reduction in the corticotrophin releasing factor levels which were reported with the extract.